3-Hydroxy-3-methylglutaryl-coenzyme, a synthase in Hevea brasiliensis - Suvachittanont W; Wititsuwannakul R (Phytochemistry, 1995)
3-Hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) synthase activity in rubber (H. brasiliensis) latex (collected from 15-year-old trees of clone RRIM 600 growing at the Songkal Rubber Research Centre) and in fractions of latex obtained by centrifugation was deterrmined using a radiochemical method. The enzyme was found in both C-serum and bottom fraction, but most was in the C-serum. H. brasiliensis leaves showed very low enzyme activity. HMG-CoA synthase in C-serum was free of HMG-CoA lyase. The enzyme in C-serum was stable at -70 C. The formation of HMG-CoA did not depend on a supply of exogenous acetoacetyle-CoA, and the rate of formation was increased as the concentration of acetyl-CoA was increased. The Km for acetyl-CoA was 9mM. The enzyme in C-serum was inhibited by several divalent cations, p-chloromercuribenzoate and dithiothreitol. Diurnal variation in the activity of the enzyme in both C-serum and extracts of leaves was observed. A positive correlation between the enzyme activity and the rubber content of the latex suggested that the enzyme regulates the synthesis of rubber in the latex.
Source Year: 1996
Keywords: 3-hydroxy-3-methylglutaryl-coenzyme; Hevea brasiliensis